Rainbow without the Sun: Textual Refraction in Soviet-era Translations - Subačius, Paulius V. (Vertimo studijos, 2023)
Light waves change direction—refract—as they pass through different environments. Similarly, Western literary works, even after leaking through the barrier of the Soviet Index Librorum Prohibitorum, never reached the USSR reader in their authentic form. The most evident components of the unfavourable environment were the proxy of the Moscow Raduga and Progress publishing houses, ideologically committed literary criticism, the hunt for honorariums, the lack of reference books, and the poverty of printing technology. All these adverse factors together caused the chronic syndrome of texts that seemed authentic but in fact were not. So far, individual agents and effects of textual refraction have been researched, and interesting case studies have been carried out. However, there is a lack of both a systematic classification of the different agents of influence and an assessment of their long-term effects. The methodological study of refraction-affected editions tests the possibility of integrating the concept of textual condition with the assertions of the postcolonial theory regarding secondary cultural colonisation. The paper attempts to raise the hypothesis that the efforts of professional translators and editors to perform their work with the utmost craftsmanship had sometimes paradoxically reinforced the refraction of the overall meaning of major literary works. That resulted from the contrast between a relatively reliable translation and the implications generated by the bibliographic code and metatexts, as well as from the canonisation of translations that had become iconic in the Soviet-era.
Keywords: Western literature; literary canon; bibliographic code; deletion; paratext; limited edition